Balassa-Samuelson and Wage, Price and Unemployment Dynamics in the Spanish Transition to EMU Membership - Javier Ordó\~nez; Katarina Jusélius (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
This paper provides an empirical investigation of the wage, price and unemployment dynamics that have taken place in Spain during the last two decades. The aim of this paper is to shed light on the impact of the European economic integration on Spanish labour market and the convergence to a European level of prosperity. We found that the Balassa-Samuelson effect, product market competition, and capital liberalization have been the main driving forces in this period. The adjustment dynamics show that Spanish inflation has adjusted in the long run to the European purchasing power parity level (as measured by the German price level) corrected for the Balassa-Samuelson effect. In the medium run this long-run convergence was achieved by two types of Phillips curve mechanisms; one where the inflation/unemployment trade-off was triggered off for different levels of the interest rate and real wage costs, another one where the trade-off was a function of the real exchange rate and the interest rate. Excess wages and/or increasing cost levels in the tradable sector led to higher unemployment rather than higher prices. Thus, much of the burden of adjustment was carried by unemployment in this period.
Keywords: C32; E24; 330; Balassa-Samuelson effect; nominal and real convergence; unemployment dynamics; purchasing power parity; cointegrated VAR; Balassa-Samuelson Effekt; Europäische Integration; Beschäftigungseffekt; Entwicklungskonvergenz; Kapitalmarktliberalisierung; Kaufkraftparität; Phillips-Kurve; Spanien